SEQUENTIAL CLOSURE OF K-CA AND RB-SR ISOTOPIC SYSTEMS IN ARCHAEAN MICAS - Fletcher I.R.; McNaughton N.J.; Pidgeon R.T.; Rosman K.J.R. (My University, 1997)
Comparative K-Ca and Rb-Sr data for extremely radiogenic muscovites (#Ca=2300 to 18,700; 87Sr/86Sr=52 to 991) from two unmetamorphosed Archaean pegmatitic rocks from the Jack Hills in the northwestern part of the Yilgarn Craton yield model ages ranging from 2580 Ma to 2100 Ma, with the K-Ca dates being younger than Rb-Sr. The muscovites occur as two textural types: radial clusters of bladed crystals (`rosettes') in a massive `pegmatitic' granite, and large euhedral `books' in cross-cutting pegmatites. There are marked differences between the dates from the two mineral forms as well as between the two isotopic systems, and no individual date can be used to provide a point for [P-]T-t plots. The data can be interpreted collectively in terms of delayed closure of the isotopic systems in a slowly cooled terrane. The closure temperature modelling demonstrates that the diffusion coefficient of Ca in muscovite is approximately an order of magnitude higher than that of Sr. A curved (assumed exponential) cooling trajectory, with extremely slow cooling (~0.1°C Ma-1) at ~2100 Ma, is required to reproduce the youngest K-Ca dates.Biotites (εCa ~150) from unmetamorphosed Archaean rocks from the southwest of the craton show differences between K-Ca and Rb-Sr model ages (Rb-Sr data from ) that resemble the differences in the Jack Hills muscovite dates. For biotites which have been affected by regional reheating at (or uplift until) ~500 Ma, the responses of the two isotopic systems are similar, but the analysed samples are not sufficiently radiogenic (εCa<40) to permit identification of any closure sequence.Muscovites with a common cooling history but differing closure temperatures define empirical cooling curves in 87Sr*/87Rb vs 40Ca*/40K plots. These can be used in conjunction with the K-Ca/Rb-Sr concordia to provide an improved minimum age estimate for the samples. When only single samples (or very similar samples) are available, the difference between the K-Ca and Rb-Sr dates gives a `quality control' indication of the discrepancy between the Rb-Sr date and crystallisation age.
Keywords: KCA; RB-SR; CLOSURE TEMPERATURE; MUSCOVITE; BIOTITE